ARSITEKTUR DAN AIR (Kasus: Kota Palembang) - Johannes Adiyanto (ATRIUM: Jurnal Arsitektur, 2017)
Title: Architecture and Water (Palembang Case) The total area of Indonesia consists of a total land area of 1,904,569 km2 and a sea area of 7.900.000 km2. Indonesia's geographical location has two rainy and dry seasons, tropical climate and high humidity and sunshine throughout the year. This condition is also reinforced by the location of Indonesia located on two continents, Asia and Australia. Thus Indonesia is not only about land but also waters. This general description becomes the basic of understanding the case study of Palembang city. The case of Palembang was appointed to see the consequences of 'water' in the course of city development and the traces of its architectural artifacts. Then how the latest development of Palembang city, is still oriented to the water or have forgotten the water as the face of the city? The purpose of this discussion is to show the development of the city, especially Palembang, related to its natural geographical conditions. Explore this descriptive paper using a historical study approach with chronic descriptive methods. Chronic descriptive method is a method of translation as it is with a note on events that are considered important in a particular location. Descriptive descriptive results show that the city of Palembang has left the water, the icon of the Musi River is placed as a 'separator / distinguishing / distance maker' rather than 'union' between Ilir and Ulu. Geographical natural conditions are not placed as a basis in the implementation and development of Palembang City.